O contexto histórico, político e econômico de orquestras sinfônicas do Brasil - Minczuk, Arcadio (2015)
This thesis entitled "The historical, political and economic context of symphony orchestras in Brazil" is based on research which presumes that "political, economic and cultural changes occurring in both national and international scenes are fueling the transformation of orchestral practices in Brazil." The research focused on political and economical changes that occurred during the defined period for this investigation - the last 30 years and, thus, allowed and enabled qualitative changes to occur in the context of symphonic ensembles in Brazil. This investigation focused on orchestral ensembles and sought to analyze groups prioritizing symphonic repertoire, which also included concertante works among other selections using choir and/ or vocal soloist. It was observed that: the connection between influential figures and entrepreneurs with ideas and consistent projects is at the heart of creation and success of quality orchestras; that changes in the international and national scene, in the late twentieth century, were crucial in the transformation of symphony orchestras in Brazil not to mention major developments in the country from 1990 to 2000.Based on this study, ranking of the five important Brazilian orchestras, some of them often referred to as world-class ensembles,include the Orquestra Sinfônica do Estado de São Paulo (Osesp), the Orquestra Sinfônica Brasileira (OSB), the Filarmônica de Minas Gerais , the Orquestra Sinfônica de Porto Alegre (Ospa) and the Orquestra Sinfônica do Teatro Nacional Claudio Santoro (OSTNCS), de Brasília. The research reveals that Osesp is unique as the most important orchestra and, coincidentally, its administration also serves as a model of excellence